2009
DOI: 10.5713/ajas.2009.80573
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymorphisms in SREBF1 and FASN Genes Affect Fatty Acid Composition in Korean Cattle (Hanwoo)

Abstract: Sterol regulatory element binding factor 1 (SREBF1) and fatty acid synthase (FASN) genes play an important role in the biosynthesis of fatty acids and cholesterol, and in lipid metabolism. This study used polymorphisms in the intron 5 of bovine SREBF1 and in the thioesterase (TE) domain of FASN genes to evaluate their associations with beef fatty acid composition. A previously identified 84-bp indel (L: insertion/long type and S: deletion/short type) of the SREBF1 gene in Korean cattle had significant associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 34 publications
1
28
2
Order By: Relevance
“…Han et al (6) found that the frequency of the S allele in the Angus and Charolais crossbred was also marginal (0.01), with the absence of the SS genotype. The estimated frequency of the S allele in Limousin cattle was 0.335, whereas the value reported by Bhuiyan et al (5) was considerably lower (0.22).…”
contrasting
confidence: 43%
See 1 more Smart Citation
“…Han et al (6) found that the frequency of the S allele in the Angus and Charolais crossbred was also marginal (0.01), with the absence of the SS genotype. The estimated frequency of the S allele in Limousin cattle was 0.335, whereas the value reported by Bhuiyan et al (5) was considerably lower (0.22).…”
contrasting
confidence: 43%
“…The short (S)-and long (L)-type alleles were identified. Recently, several studies have indicated an association between this ins/ del polymorphism and fatty acid composition in the milk and meat of cattle (2,(4)(5)(6). The aim of this study was to analyze the genotype distribution of the above-mentioned polymorphism in cattle populations of different breeds.…”
mentioning
confidence: 99%
“…Furthermore, in a study of five different breeds, this polymorphism was only found in the Limousine breed, suggesting that it might be a breed-specific phenomenon and may not be segregating widely in different cattle populations (Bhuiyan et al, 2009). In the present study, Snow Dragon black cattle showed a slightly higher frequency of the SS genotype compared to Simmental bulls, which may be due to its long history of selective breeding.…”
Section: Discussionmentioning
confidence: 45%
“…In contrast, the stearic acid concentration was 6.30% lower in the SS genotype compared to the LL genotype (P < 0.05), but the linoleic and PUFA contents were 11.06 and 12.20% higher in SS compared to LL (Bhuiyan et al, 2009). Several studies have reported associations between SREBP1 and fatty acid composition and carcass traits.…”
Section: Discussionmentioning
confidence: 84%
“…The FASN gene has seven active sites that help to catalyze all the reaction steps in the conversion of acetyl-CoA and malonyl-CoA to palmitate (Roy et al, 2005). Several reports indicated that the mutations in FASN gene were associated with (Bhuiyan et al, 2009;Lee et al, 2010;Zhang et al, 2008). Also, the polymorphisms in chicken FASN gene have been reported by Marrube et al (2004) and this gene is located on chromosome 18 and had three TE domains in exons 40, 41 and 42 (Kasturi et al, 1988).…”
Section: Introductionmentioning
confidence: 95%